2003
DOI: 10.2337/diabetes.52.10.2483
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance in the Liver-Specific IGF-1 Gene-Deleted Mouse Is Abrogated by Deletion of the Acid-Labile Subunit of the IGF-Binding Protein-3 Complex

Abstract: Liver IGF-1 deficient (LID) mice demonstrate a 75% reduction in circulating IGF-1 levels and a corresponding fourfold increase in growth hormone (GH) levels. At 16 weeks of age, LID mice demonstrate, using the hyperinsulinemic-euglycemic clamp, insulin insensitivity in muscle, liver, and fat tissues. In contrast, mice with a gene deletion of the acid-labile subunit (ALSKO) demonstrate a 65% reduction in circulating IGF-1 levels, with normal GH levels and no signs of insulin resistance. To further clarify the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
1
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 42 publications
2
77
1
4
Order By: Relevance
“…Despite this, the mechanisms for multigenerational inheritance observed here are thus far unclear. Aside from its role in growth and development, low levels of IGF-1, like those seen accompanying increased methylation following placental insufficiency (33), is critical to later glucose homeostasis and insulin resistance (37,72,73). Our findings herein significantly contribute to the role of epigenomic modifications in both regulating IUGR-mediated adult MetS and an accompanying variation in IGF-1 expression and demonstrate a favorable impact of one-carbon intermediate supplementation.…”
Section: Discussionmentioning
confidence: 58%
“…Despite this, the mechanisms for multigenerational inheritance observed here are thus far unclear. Aside from its role in growth and development, low levels of IGF-1, like those seen accompanying increased methylation following placental insufficiency (33), is critical to later glucose homeostasis and insulin resistance (37,72,73). Our findings herein significantly contribute to the role of epigenomic modifications in both regulating IUGR-mediated adult MetS and an accompanying variation in IGF-1 expression and demonstrate a favorable impact of one-carbon intermediate supplementation.…”
Section: Discussionmentioning
confidence: 58%
“…The key distinction between our protocol and that of others is that we use an arterial catheter for obtaining blood samples. This is in contrast to the more widely used approach of obtaining blood samples by severing the tip of the tail 4,7,11,12,[14][15][16][17] . The advantage of sampling from an arterial catheter is that the experiment is conducted in a conscious and unrestrained mouse.…”
Section: Discussionmentioning
confidence: 93%
“…We indirectly determined this possibility by measuring the serum levels of IGFBP3 and ALS, two proteins that form a ternary complex with IGF1 that is believed to block IGF1 from crossing the blood vessels and from being degraded in the blood (Rajaram et al 1997, Boisclair et al 2001, Firth & Baxter 2002. Such roles of IGFBP3 and ALS are supported by many studies (Ueki et al 2000, Boisclair et al 2001, Modric et al 2001, Haluzik et al 2003, Hwa et al 2006, Domene et al 2007. Our study showed that GH injection caused a greater increase in both serum IGFBP3 and ALS protein levels in the cows fed additional concentrates than in the cows fed hay only, and that post-GH injection serum concentrations of both IGFBP3 and ALS were greater in the cows fed additional concentrates than in the cows fed hay only.…”
Section: Discussionmentioning
confidence: 99%
“…For example, liver overexpression of IGF1 increased serum IGFBP3 concentration in addition to serum IGF1 concentration (Camacho-Hubner et al 1991, Liao et al 2006. Liver-specific inactivation of the IGF1 gene not only reduces serum IGF1 concentration, but also reduces serum IGFBP3 and ALS concentrations (Yakar et al 2002, Haluzik et al 2003. Therefore, it is possible that the greater increases in serum protein levels of IGFBP3 and ALS in response to GH under increased nutrition initially are a result rather than a cause of the greater increase in serum IGF1 concentration.…”
Section: Discussionmentioning
confidence: 99%